Age at onset of Huntington disease is not modulated by the R72P variation in TP53 and the R196K variation in the gene coding for the human caspase activated DNase (hCAD) - Andrich Jürgen; Saft Carsten; Kraus Peter H; Arning Larissa; Epplen Jörg T (BMC, 2005)
Abstract Background TP53 is an attractive candidate for modifying age of onset (AO) in Huntington disease (HD): The amino-terminus of the mutated huntingtin (htt) exon 1 translation product has functional properties which may affect critically the TP53 pathway in HD neurons. The pathogenic domain of mutant htt interacts with nuclear transcription factors, and it potentially modulates TP53-induced transcriptional events. A single nucleotide polymorphism (SNP) resulting in the R72P exchange in TP53 protein might modulate the variation in AO. In addition, also the R196K replacement in human caspase activated DNase (hCAD) may theoretically affect the AO. Methods We have genotyped the polymorphisms R72P and R196K in a well established cohort of 167 unrelated HD patients. Results The expanded CAG repeat explained 30.8% of the variance in AO. Adding the genotypes of the SNPs investigated did not affect the variance of the AO variance explained. Conclusion In this replication study, no association was found explaining a significant amount of the variability in AO of HD thus contradicting a recent report.